Correlations between Changes in Medical Opioid Dispensing and Contributions of Fentanyl to Opioid-Related Overdose Fatalities: Exploratory Analyses from Canada - Jones, Wayne (Int J Environ Res Public Health, 2021)
Canada is experiencing an epidemic of opioid-related mortality, with increasing yet heterogeneous fatality patterns from illicit/synthetic (e.g., fentanyl) opioids. The present study examined whether differential provincial reductions in medical opioid dispensing following restrictive regulations (post-2010) were associated with differential contributions of fentanyl to opioid mortality. Annual provincial opioid dispensing totals in defined daily doses/1000 population/day, and change rates in opioid dispensing for the 10 provinces for (1) 2011–2018 and (2) “peak-year” to 2018 were derived from a pan-Canadian pharmacy-based dispensing panel. Provincial contribution rates of fentanyl to opioid-related mortality (2016–2019) were averaged. Correlation values (Pearson’s R) between provincial changes in opioid dispensing and the relative fentanyl contributions to mortality were computed for the two scenarios. The correlation between province-based changes in opioid dispensing (2011–2018) and the relative contribution of fentanyl to total opioid deaths (2016–2019) was −0.70 (t = 2.75; df = 8; p = 0.03); the corresponding correlation for opioid dispensing changes (“peak-year” to 2018) was −0.59 (t = −2.06; df = 8; p = 0.07). Provincial reductions in medical opioid dispensing indicated (near-)significant correlations with fentanyl contribution rates to opioid-related death totals. Differential reductions in pharmaceutical opioid availability may have created supply voids for nonmedical use, substituted with synthetic/toxic (e.g., fentanyl) opioids and leading to accelerated opioid mortality. Implications of these possible unintended adverse consequences warrant consideration for public health policy.